The Deposit Business at Large vs. Small Banks - Avernas, Adrien d',Eisfeldt, Andrea L.,Huang, Can,Stanton, Richard,Wallace, Nancy E. (National Bureau of Economic Research, 2023)
The deposit business differs at large versus small banks. We provide a parsimonious model and extensive empirical evidence supporting the idea that much of the variation in deposit-pricing behavior between large and small banks reflects differences in
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Einlagengeschäft; Bank; Betriebsgröße; Großbank; Preismanagement; Bankenliquidität; Financial Markets and the Macroeconomy; General; Financial Institutions and Services; Banks; Depository Institutions; Micro Finance Institutions; Mortgages; Government Policy and Regulation